Pathology and biopsy assessment of non-alcoholic fatty liver disease - Straub, Beate Katharina; Schirmacher, Peter (Digestive diseases, 2010)
Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent liver diseases in Western industrialized countries with dramatically rising incidence. The diagnosis of NAFLD requires the existence of steatosis in the absence of significant alcohol consumption. In cases of relevant inflammation pathogenetically linked to steatosis, it is termed non-alcoholic steatohepatitis (NASH). While pure steatosis represents a relatively harmless and rapidly reversible condition without a significant tendency to progression, NASH carries a significant morbidity and progression risk. Noninvasive methods neither reliably establish the diagnosis nor define the extent of disease in NASH, making histopathology the diagnostic gold standard. Since current therapeutic options in NASH are limited, indication for biopsy is made in the clinical context, predominantly in unclear clinical constellations, prior to invasive measures, for follow-up purposes and in the context of clinical studies. Histological hallmarks of NASH are steatosis, hepatocellular ballooning (with and without Mallory-Denk bodies), necroinflammation, and progressing disease a characteristic with perisinusoidal fibrosis. For semiquantitative assessment of necroinflammation (grading) and fibrosis (staging), a score has recently been implemented. Although histology does not reliably distinguish alcoholic steatohepatitis/alcoholic fatty liver disease from NASH/NAFLD, it may give valuable hints. NASH has a tendency for more steatosis, the so-called glycogenated nuclei, and less necroinflammatory activity. Future development of biopsy diagnosis will be coupled to the development of differential systemic therapeutic approaches. Especially in the context of clinical studies, detailed histological evaluation should be considered for the detection of predictive parameters.
Gesehen am 01.09.2023